2015
DOI: 10.1038/pr.2015.197
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and trauma informed care: the future of health care

Abstract: Adverse childhood experiences (ACEs) are related to shortand long-term negative physical and mental health consequences among children and adults. Studies of the last three decades on ACEs and traumatic stress have emphasized their impact and the importance of preventing and addressing trauma across all service systems utilizing universal systemic approaches. Current developments on the implementation of trauma informed care (TIC) in a variety of service systems call for the surveillance of trauma, resiliency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
252
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 366 publications
(300 citation statements)
references
References 62 publications
4
252
1
2
Order By: Relevance
“…The Behavioral Risk Factor Surveillance System (BRFSS) began collecting ACE data after the CDC-Kaiser ACE Study was completed on childhood neglect and abuse, among other (Cranston & Davis, 2011;Najavits & Hien, 2013;Oral et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Behavioral Risk Factor Surveillance System (BRFSS) began collecting ACE data after the CDC-Kaiser ACE Study was completed on childhood neglect and abuse, among other (Cranston & Davis, 2011;Najavits & Hien, 2013;Oral et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Interventions for trauma geared towards women were examined, however, both males and females are equally affected (CDC, 2010). Additional research and funding is needed for this high-risk population, given the existing research specific to women with co-occurring trauma and SUD have demonstrated poor outcomes when trauma is not identified during initial evaluation (Cranston & Davis, 2011;Najavits & Hien, 2013;Oral et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations